2020
DOI: 10.1002/rcm.8831
|View full text |Cite
|
Sign up to set email alerts
|

Identification of short‐chain fatty acid esters of hydroxy fatty acids (SFAHFAs) in a murine model by nontargeted analysis using ultra‐high‐performance liquid chromatography/linear ion trap quadrupole‐Orbitrap mass spectrometry

Abstract: RationaleFatty acid esters of hydroxy fatty acids (FAHFAs) are recently discovered endogenous lipids with outstanding health benefits. FAHFAs are known to exhibit antioxidant, antidiabetic and anti‐inflammatory properties. The number of known long‐chain FAHFAs in mammalian tissues and dietary resources increased recently because of the latest developments in high‐resolution tandem mass spectrometry techniques. However, there are no reports on the identification of short‐chain fatty acid esterified hydroxy fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 31 publications
5
35
0
Order By: Relevance
“…So far, the FAHFAs identified are esterified at carbon chain≥C5 [ 5 , 10 ], but esters at C2 position are limited [ 11 ]. In our previous study, we have confirmed that the location of the hydroxy group is at C-2 of long-chain fatty acid by MS n analysis [ 12 ]. Further successive loss of neutral molecules of CH2=CO ( m / z 42 Da) and H 2 O ( m / z 18 Da) from the fragment ion m / z 396 gives a molecular ion at m / z 354 and m / z 336, respectively.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…So far, the FAHFAs identified are esterified at carbon chain≥C5 [ 5 , 10 ], but esters at C2 position are limited [ 11 ]. In our previous study, we have confirmed that the location of the hydroxy group is at C-2 of long-chain fatty acid by MS n analysis [ 12 ]. Further successive loss of neutral molecules of CH2=CO ( m / z 42 Da) and H 2 O ( m / z 18 Da) from the fragment ion m / z 396 gives a molecular ion at m / z 354 and m / z 336, respectively.…”
Section: Resultssupporting
confidence: 53%
“…As the data shows, signal intensity of DMED-SFAHFA is increased by almost three folds higher compared to unlabeled SFAHFA. Though this change is small, it contributes largely to the detection of other minor SFAHFAs, which were unidentified in our previous study [ 12 ]. Table 1 shows the list of SFAHFAs identified after DMED labeling, which includes additional six new molecular species which were identified in this study.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations